Exploring the Relationship Between Corporate Goernance Mechanism and Financial Performance : Evidence From Listed Companies - Mohammad Rizky Yahya (Westscience Press, 2023)
This study examines, through quantitative analysis, the relationship between corporate governance practices and financial performance of a listed company in West Java, Indonesia. The research examines important financial performance measures, such as Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS), using secondary data from annual reports, financial statements, and corporate governance disclosures. Various corporate governance practices are examined as independent variables, including board composition, ownership structure, CEO compensation, and audit quality. The study uses multiple regression analysis and correlation analysis to reveal significant associations between corporate governance practices and financial performance. The findings provide important insights for regulators, investors and business leaders to strengthen corporate governance standards and achieve long-term financial success in West Java's turbulent economic environment.